2018
DOI: 10.1002/ente.201700960
|View full text |Cite
|
Sign up to set email alerts
|

Hot‐Pressed Hybrid Electrodes Comprising Silver Nanowires and Conductive Polymers for Mechanically Robust, All‐Doctor‐Bladed Semitransparent Organic Solar Cells

Abstract: Future low‐cost, high‐throughput production of organic solar cells in roll‐to‐roll printing processes calls for all‐solution‐processable device architectures. Mechanical flexibility and robustness are mandatory to roll the solar foils during printing and to eventually comply with certain end‐user requirements. Here, we report on semitransparent organic solar cells, comprising top and bottom silver nanowire (AgNW) electrodes that were embedded into conductive poly(3,4‐ethylenedioxythiophene):poly(styrenesulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…In addition, this hybrid electrode displays good wetting on glass, PET and active layers. Using the doctor-bladed PET/Ag mesh/PEDOT:PPS bottom electrode and PEDOT:PSS:AgNW top electrode (Figure 23f), Colsmann and coworkers achieved semi-transparent fully printed OSCs with PCEs of 6.6% on small areas (0.1 cm 2 ) and 5.9% on large areas (>1 cm 2 ), Ag NW <5 10-20 Ω □ −1 >80 10-30 [350,[421][422][423][424][425] Ag NP 10-13 <1 Ω □ −1 Opaque <10 [226,426] Ag precursor <100 1 Ω □ −1 Opaque 3.3 [280] Cu NW -15-24 Ω □ −1 >80 - [427,428] CNT -50-200 Ω □ −1 >70 <20 [429][430][431][432] Carbon -<10 Ω □ −1 Opaque - [433,434] Graphene -<600 Ω □ −1 >85 <10 [435][436][437] PANi <300 <20 S cm −1 <70 - [438,439] PPy -<40 S cm −1 <70 44 [440] PEDOT:PSS 15-60 <100 Ω □ −1 >80 <5 [14,152,175] PEDOT:PSS:AgNWs 20 10-40 Ω □ −1 >80 11 [441] S-PEDOT 24.3 1089 S cm −1 >80 0.4 [106] www.afm-journal.de www.advancedsciencenews.com…”
Section: Fully Printed Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this hybrid electrode displays good wetting on glass, PET and active layers. Using the doctor-bladed PET/Ag mesh/PEDOT:PPS bottom electrode and PEDOT:PSS:AgNW top electrode (Figure 23f), Colsmann and coworkers achieved semi-transparent fully printed OSCs with PCEs of 6.6% on small areas (0.1 cm 2 ) and 5.9% on large areas (>1 cm 2 ), Ag NW <5 10-20 Ω □ −1 >80 10-30 [350,[421][422][423][424][425] Ag NP 10-13 <1 Ω □ −1 Opaque <10 [226,426] Ag precursor <100 1 Ω □ −1 Opaque 3.3 [280] Cu NW -15-24 Ω □ −1 >80 - [427,428] CNT -50-200 Ω □ −1 >70 <20 [429][430][431][432] Carbon -<10 Ω □ −1 Opaque - [433,434] Graphene -<600 Ω □ −1 >85 <10 [435][436][437] PANi <300 <20 S cm −1 <70 - [438,439] PPy -<40 S cm −1 <70 44 [440] PEDOT:PSS 15-60 <100 Ω □ −1 >80 <5 [14,152,175] PEDOT:PSS:AgNWs 20 10-40 Ω □ −1 >80 11 [441] S-PEDOT 24.3 1089 S cm −1 >80 0.4 [106] www.afm-journal.de www.advancedsciencenews.com…”
Section: Fully Printed Solar Cellsmentioning
confidence: 99%
“…[450] Copyright 2017, Wiley-VCH. OSCs 2013 PET/Ag grid/PEDOT:PSS/ZnO/P3HT:PC 61 BM/PEDOT:PSS/Ag grid Screen printing F, R, module,66 cm 2 1.6 [447] 2013 PET/Ag grid/PEDOT:PSS/ZnO/PDTSTTz-4:PC 61 BM/PEDOT:PSS/Ag grid Screen printing F, R, 1 cm 2 3.5 [448] 2014 PET/Ag grid/PEDOT:PSS/ZnO/tandem/HTL/PEDOT:PSS/Ag grid Slot-die F, R, module, 52.2 cm 2 1.76 [442] 2014 PET/Ag grid/PEDOT:PSS/ZnO/tandem/PEDOT:PSS Slot-die F, R, 1 cm 2 1.36 [456] 2014 PES/PEDOT:PSS c) /PEI/P3HT:ICBA/PEDOT:PSS Film-transfer lamination S, 0.04 cm 2 2.4 [241] 2014 Glass/PEDOT:PSS/PCDTBT:PC 71 BM/ZnO/Ag NP Inkjet printing F, 0.5 cm 2 2.05 [228] 2015 PET/Ag grid/PEDOT:PSS/ZnO/PBDTTTz-4:PC 61 BM/HTL/carbon Screen printing F, R, module, 28.8 cm 2 3.8 [444] 2015 PEN/PEDOT:PSS/PEI/PTB7-Th:PC 71 BM/Ca/Al Film-transfer lamination 0.046 cm 2 7.7 [175] 2015 Glass/Ag gird/PEDOT:PSS/ZnO/P3HT:PC 61 BM/PEDOT:PSS/Ag Inkjet printing F, >1 cm 2 4.1 [226] 2016 PET/Ag grid/PEDOT:PSS/ZnO/PTB7-Th:IEIC/PEDOT:PSS/Ag grid Screen printing F, R, 0.98 cm 2 1.79 [449] 2016 PET/Ag mesh/PEDOT:PSS/ZnO/PffBT4T-2OD:PC 61 BM:PC 71 BM/PEDOT:PSS:Ag NW Doctor blading F, >1 cm 2 5.9 [415] 2017 PET/Ag/ZnO/PBTZT-stat-BDTT8:PC 61 BM:PC 71 BM/PEDOT:PSS:Ag NW Doctor blading F, module, 17.7 cm 2 2.9 [450] 2018 PET/PEDOT:PSS:Ag NW/ZnO/PBTZT-stat-BDTT8:PC 61 BM:PC 71 BM/PEDOT:PSS:Ag NW Doctor blading F, 0.5 cm 2 3.8 [441] 2018 PES/PEDOT:PSS/P3HT:ICBA:PEI/PEDOT:PSS Maobi-coating S, 0.1 cm 2 3.28 [240] 2020 Ag NW@PI/ZnO/PM6:Y6:IDIC/HxMoO 3 /PEDOT:PSS/Ag NW Film-transfer lamination S, 1 cm 2 10.3 [454] PerSCs 2016 FTO/c-TiO 2 /m-TiO 2 /MAPbI 3−X Cl X /Spiro-OMeTAD/PEDOT:PSS Film-transfer lamination 0.04 cm 2 15.4 [367] 2017 PET/PEDOT:PSS c) /ZnO/perovskite/Spiro-OMeTAD/PEDOT:PSS Film-transfer lamination S, 0.11 cm 2 10.3 [176] a) Method refers to printing process of PEDOT electrode; b) F denotes all function layer are printed; R denotes R2R production; S denotes all function layer are solutionprocessed; c) PEDOT:PSS electrode is fabricated by spin-coating.…”
Section: (36 Of 46)mentioning
confidence: 99%
“…Recently, Koppitz et al embedded the Ag NWs into the conducting polymer PEDOT:PSS to fabricate the transparent electrode for ST‐OSCs. [ 122 ] They demonstrated that PEDOT:PSS and Ag NWs hybrid electrodes can be effectively used as both top and bottom electrodes in the device. With a device structure of PET:PEDOT:PSS:AgNW/ZnO/PBTZT‐stat‐BDTT‐8:PCBM/PEDOT:PSS:AgNW, the ST‐OSC showed a PCE of 3.80% with an AVT of 25%.…”
Section: Strategies and Progressmentioning
confidence: 99%
“…If a choice is made for solution deposition, it may be advisable to replace the vacuum processes that are used in research laboratories to apply the conductive electrodes, by solution processes as well. Latest efforts targeted the replacement of indium tin oxide (ITO) electrodes and metal counter electrodes, e.g., by conductive polymers, [69] often supported by printed silver [70] or random metal nanowire [71] grids, as exemplified in Figure 5. The generally reduced conductivity and increased resistivity of printed electrodes requires a smart current management in large-scale solar cells, which is typically accomplished by implementing a monolithic interconnection: as shown in Figure 6a, the series connection of the individual solar cells increases the voltage of the module while reducing the photocurrent, the latter of which accounts for resistive losses in the electrodes.…”
Section: Process Scaling By Printingmentioning
confidence: 99%